(untitled) (City: History, Culture, Society, 2020)
The article deals with the transformation of “places of memory” in post-Soviet Kyiv’s cultural space based on the case of January Uprising Street. The main attention focuses on three events crucial for Ukrainian history in the twentieth century: the 1917–1921 Ukrainian Revolution, Holodomor and the Second World War. The author highlights the change in the ideological connotation and cultural representations of Soviet “places of memory” during almost thirty years of Ukrainian independence. The former January Uprising Street, which today consists of two streets – Ivan Mazepa and Lavrska – would for a long period of time signify the key events of Soviet history: October Revolution Civil war and World War II. The Park of Eternal Glory and Memorial complex “Ukrainian State Museum of the History of the Great Patriotic War of 1941–1945” (now known as the National Museum of the history of Ukraine in the Second World War) built into the historical space pf the ancient Kyiv had to propagate the main Soviet historical event. After Ukraine gained independence the space along the former January Upraising Street has transformed greatly. The public space has been affected by the rediscovery of forgotten and erased events.